Anisotropic adaptive method for triangular meshes smoothing. Issue 6 (1st June 2015) - El Ouafdi, Ahmed Fouad; El Houari, Hassan; Ziou, Djemel
Abstract : Even with the advancing laser scanner technology, the digital objects are inevitably corrupted with random noise during the acquisition process. Many algorithms, regardless of principle, share the same basic idea of noise reduction through mesh smoothing. Smoothing can be performed locally, as in the anisotropic filtering by calculus of variations; or by smoothing mesh attributes such as normal vector and then adjusting vertex positions. In this study, the authors propose a novel algorithm based on the statistical distribution noise for anisotropic mesh smoothing. In this approach, the probability density function of the noise is first estimated, and then the anisotropic smoothing operation is performed through the diffusion tensor that allows to preserve mesh characteristics like edges, corner and ridges. The proposed algorithm is easy to implement and is thus suitable for real‐time noise reduction application.